Predictive factors and outcomes of immune-related adverse events in Chinese patients treated with immune checkpoint inhibitors: a real-world retrospective study - Kong, Haodong; Xie, Rongjia; Liu, Zhuqing (Frontiers in Immunology, 2025)
BackgroundThe widespread clinical application of immune checkpoint inhibitors (ICIs) has brought immune-related adverse events (irAEs) to the forefront of oncology management. However, systematic investigations focusing on the efficacy and irAE profiles of ICIs locally developed in China (Chinese ICIs) in real-world settings remain limited. This study aimed to explore predictive factors and outcomes of irAEs in patients predominantly treated with Chinese ICIs.MethodsIn this single-center retrospective study, 206 patients with solid tumors treated with ICIs between 2020 and 2024 were included, with 87.9% receiving Chinese ICIs. Multivariate regression analyses were conducted to identify predictors of irAEs and factors associated with progression-free survival (PFS). Clinical characteristics, inflammatory biomarkers, cytokine levels, and cardiac function parameters were comprehensively evaluated.ResultsYounger age (p=0.04) and the brain metastases (p=0.03) were associated with a higher incidence of irAEs. Organ-specific irAEs showed distinct predictors: hepatitis with younger age, hepatitis B virus (HBV) infection, hepatic malignancy, multisystem irAEs, and elevated IL-10; myocarditis with multisystem irAEs, systemic inflammation markers (white blood cell count, WBC; neutrophil-to-lymphocyte ratio, NLR; systemic immune-inflammation index, SII; systemic inflammation response index, SIRI), and cardiac function indicators (left ventricular ejection fraction, LVEF; QRS duration); thyroiditis with multisystem irAEs and reduced IL-6; while pneumonitis with elevated platelet count (PLT) and IL-6. The type of irAEs was not associated with PFS.ConclusionsYounger age and brain metastases were associated with a higher incidence of irAEs. Organ-specific irAEs were characterized by distinct sets of clinical and laboratory predictors. Inflammatory markers correlated with poorer PFS. The type of irAEs was not associated with PFS. Chinese ICIs were not independently associated with an increased risk of specific organ toxicities.